Epidemiology and Related Risk Factors of Preterm Labor as an Obstetrics Emergency - Halimi Asl, Ali Asghar; Safari, Saeed; Parvareshi Hamrah, Mohsen (Archives of Academic Emergency Medicine, 2017)
Introduction: Preterm birth is still a major health problem throughout the world, which results in 75% of neonatal mortality. Preterm labor not only inflicts financial and emotional distress, it may also lead to permanent disability. The present study was conducted to determine the related risk factors and preventive measures of preterm labor. Methods: This retrospective cross-sectional study assessed all preterm labors, as well as an equal number of term labors, during seven years, at an educational hospital. Probable risk factors of preterm labor were collected using medical profiles of participants by the aid of a pre-designed checklist. Significant related factors of preterm labor were used for multivariate logistic regression analysis with SPSS 21.0. Result: 810 cases with the mean age of 28.33 ± 6.1 years were evaluated (48.7% preterm). Multipartite; fetal anomaly; prenatal care; smoking; not consuming folic acid and iron supplements; in vitro fertilization; history of infertility, caesarian section, trauma, systemic disease, and hypertension; amniotic fluid leak; rupture of membranes; cephalic presentation; vaginal bleeding; placenta decolman; oligohydramnios; pre-eclampsia; chorioamnionitis; uterine abnormalities; cervical insufficiency; intercourse during the previous week; short time since last delivery; and mother’s weight significantly correlated with preterm labor. Conclusion: Based on the results of the present study, intercourse during the previous week, multipartite, short time from last delivery, preeclampsia, fetal anomaly, rupture of membranes, hypertension, and amniotic fluid leak, respectively, were risk factors for preterm labor. On the other hand, iron consumption, cephalic presentation, systematic disease, history of caesarian section, prenatal care, and mother’s weight could be considered as protective factors.